2022
DOI: 10.1007/s12546-021-09271-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of life expectancy due to respiratory infectious diseases: findings from the global burden of disease study in 195 countries and territories 1990–2017

Abstract: Understanding of the patterns of and changes in mortality from respiratory infectious diseases (RID) and its contribution to loss of life expectancy (LE) is inadequate in the existing literature. With rapid sociodemographic changes globally, and the current COVID-19 pandemic, it is timely to revisit the disease burden of RID. Using the approaches of life table and cause-eliminated life table based on data from the Global Burden of Disease Study (GBD), the study analyses loss of LE due to RID in 195 countries/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…COVID-19 is a respiratory infectious disease (RID) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Zhang et al, 2022a , Zhang et al, 2022b ). RID poses a huge threat to the population and public health, and recent studies have found that the loss of life expectancy due to RID stood at 1.29 years in 2017 globally ( Huang and Guo, 2022 ). To live with the ongoing challenges by COVID-19 or the re-emergence of other respiratory viral infections, people must raise awareness and take measures for infection prevention and control in daily life ( Coccia, 2021 ; Zhu and Zhu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a respiratory infectious disease (RID) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( Zhang et al, 2022a , Zhang et al, 2022b ). RID poses a huge threat to the population and public health, and recent studies have found that the loss of life expectancy due to RID stood at 1.29 years in 2017 globally ( Huang and Guo, 2022 ). To live with the ongoing challenges by COVID-19 or the re-emergence of other respiratory viral infections, people must raise awareness and take measures for infection prevention and control in daily life ( Coccia, 2021 ; Zhu and Zhu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is a respiratory infectious disease (RID) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Zhang et al, 2022a). RID poses a huge threat to the population and public health, and recent studies have found that the loss of life expectancy due to RID stood at 1.29 years in 2017 globally (Huang and Guo, 2021). To live with the ongoing challenges by COVID-19 or the re-emergence of other respiratory viral infections, people must raise awareness and take measures for infection prevention and control in daily life (Coccia, 2021;Zhu and Zhu, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of infectious disease has been large, with a higher share in less developed countries (1)(2)(3)(4). With the advent of the COVID-19 pandemic the developed world was sensitized to the field with awakened interest and its funding and research output increased rapidly (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Infectious diseases are an important field in medicine, epidemiology, and public health across a spectrum that spans basic science, translational research, clinical and population-level applications. The global burden of infectious disease has been large, with a higher share in less developed countries(14). With the advent of the COVID-19 pandemic the developed world was sensitized to the field with awakened interest and its funding and research output increased rapidly(57).…”
Section: Introductionmentioning
confidence: 99%